Design and Synthesis of AIE-Based Small-Molecule and Nanofibrous Film for Fluorescent Sensing Application - Ma, Chunping; Li, Zhiyi; Zhang, Chenglin; Xie, Gaoyi; Wu, Yancheng; Zhang, Yangfan; Mo, Jinpeng; Liu, Xi; Wang, Ke; Xie, Dong; Li, Yang (Frontiers in Chemistry, 2021)
Fluorescent sensors that respond to environmental conditions (temperature, pressure, and pH) have attracted widespread attention in recent years. Generally, traditional solid-state fluorescent materials tend to suffer from aggregation-induced quenching (ACQ) and difficulty of film forming, limiting their extensive applications. Therefore, researchers are focusing more and more attention on fluorescent sensors with aggregation-induced emission (AIE) effects. Herein, the article reports an AIE molecule (TPEBZMZ) containing tetraphenylethylene (TPE) and benzimidazole fragments. The fluorescence properties of TPEBZMZ in solution and aggregation states have been investigated, and the luminescence performance and aggregation structures of solid-state TPEBZMZ after force and acid treatments have been explored. The results show obvious AIE and fluorescent sensing properties of TPEBZMZ, presenting force- and acid-induced discolorations. Moreover, the TPEBZMZ-based fluorescent nanofibrous film is fabricated by electrospinning the solution of TPEBZMZ blended with polylactic acid (PLA), which shows a good nanofiber film structure and exhibits reversible acid-induced discoloration property, even with only 0.5 wt% TPEBZMZ. This work provides a simple strategy to achieve stimulus-responsive fluorescent film.